Opening an Absolute Majority A Typology of Motivations for Opening and Selecting Coalition Partners - Grandjean, Geoffrey; Meens, Valentine (Politics of the Low Countries, 2025)
Following the municipal elections in the Walloon Region (Belgium) on 14 October 2018, 189 political groups won an absolute majority. Twenty-two of these decided not to exercise power alone, but favoured the formation of an oversized coalition by integrating a minority partner. The aim of this article is to identify the motivations behind the formation of a local coalition when one of the partners has an absolute majority. Semi-structured interviews with mayors and leaders of political groups in these municipalities make it possible to identify the motivations for, first, the choice to open and, second, the choice of a minority partner. By distinguishing between necessary and supporting motivations, this article shows that the search for greater representation is a necessary motivation for the choice to open, whereas personal affinities and memories of the past are necessary motivations for choosing minority partners. By prioritising motivations, this article shows that.